Immunogenicity of Influenza Vaccination in Patients With Cancer. (March 2018) - Waqar, Saiama N.; Boehmer, Leigh; Morgensztern, Daniel; Wang-Gillam, Andrea; Sorscher, Steven; Lawrence, Steven; Gao, Feng; Guebert, Kalin; Williams, Kristina; Govindan, Ramaswamy
Abstract : Background: Influenza leads to significant morbidity and mortality in patients with cancer. Patients with cancer receiving chemotherapy may not mount an adequate immune response to the vaccine. We performed this pilot study to evaluate the immunogenicity of influenza vaccination in patients with cancer receiving chemotherapy. Materials and Methods: During the 2011 to 2012 influenza season, patients undergoing chemotherapy for solid tumors were given trivalent inactivated influenza vaccine either on the day of chemotherapy (schedule A) or a week before chemotherapy (schedule B) by a single 0.5 mL injection in the deltoid muscle region. This was not a randomized trial. Hemagglutination inhibition assays were performed on blood samples from these patients taken at baseline, and 4 weeks postvaccination. Seroconversion rate (>4-fold increase in titers) and seroprotection rates (postvaccination titers of >1:40) were calculated for each vaccine component: influenza A (H1N1), A (H3N2) and B. Results: A total of 18 patients received influenza vaccination as part of this pilot study. Of these, 8 patients received the vaccine on schedule A and 10 patients received the vaccine on schedule B. Geometric mean titers against each strain significantly improved after vaccination for both groups, as measured by signed rank test. Seroconversion to at least 1 strain was observed in 75% of patients on schedule A, and 70% of patients vaccinated on schedule B. Seroprotection to at least 1 strain was observed in 100% of patients in the schedule A group, and 60% of patients vaccinated on schedule B. Seroconversion and seroprotection rates against the 3 influenza strains were not significantly different between the 2 groups. Conclusions: Patients with nonhematological malignancies who are receiving chemotherapy mount an immune response to influenza vaccination. Timing of influenza vaccination in relation to chemotherapy does not seem to matter.